1997
DOI: 10.1109/34.601251
|View full text |Cite
|
Sign up to set email alerts
|

Structural matching by discrete relaxation

Abstract: Abstract-This paper describes a Bayesian framework for performing relational graph matching by discrete relaxation. Our basic aim is to draw on this framework to provide a comparative evaluation of a number of contrasting approaches to relational matching. Broadly speaking there are two main aspects to this study. Firstly we focus on the issue of how relational inexactness may be quantified. We illustrate that several popular relational distance measures can be recovered as specific limiting cases of the Bayes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
181
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(183 citation statements)
references
References 37 publications
0
181
0
2
Order By: Relevance
“…We also compare the results with four alternative algorithms. These are the original discrete relaxation method of Wilson and Hancock [8] which is applied to overlapping supercliques, the quadratic assignment method of Gold and Rangarajan [20], the non-quadratic graduated assignment method of Finch et al [21], and, the singular value decomposition method of Luo and Hancock [7]. In Fig.…”
Section: Sensitivity Studymentioning
confidence: 99%
See 1 more Smart Citation
“…We also compare the results with four alternative algorithms. These are the original discrete relaxation method of Wilson and Hancock [8] which is applied to overlapping supercliques, the quadratic assignment method of Gold and Rangarajan [20], the non-quadratic graduated assignment method of Finch et al [21], and, the singular value decomposition method of Luo and Hancock [7]. In Fig.…”
Section: Sensitivity Studymentioning
confidence: 99%
“…These two methods fail when the graphs being matched contain different numbers of nodes. However, this problem can be overcome by using the apparatus of the EM algorithm [7,8]. More recently, Shokoufandeh et al [9] have shown how graphs can be retrieved efficiently using an indexing mechanism that maps the topological structure of shock-trees into a low-dimensional vector space.…”
Section: Introductionmentioning
confidence: 99%
“…with good color continuity, which can be obtained from either the color segmentation algorithm described above, or any other method such as the one described in [3]. This set of regions is further divided in two subsets.…”
Section: Fusion Of Colour-based Segmentation and Depth From Stereomentioning
confidence: 99%
“…Nevertheless, new developments in approximation algorithms for graph matching have allowed the reduction of this time complexity for sub-optimal solutions (see for example Refs. [3,4]). …”
Section: Introductionmentioning
confidence: 99%
“…In relaxation techniques [24] [25] [10], all locally consistent assignments are made first (short horizon distance). Then the horizon is effectively increased via a constraint propagation that occurs in an iterative fashion.…”
Section: Approximate Techniquesmentioning
confidence: 99%